LRRK2 G2385R and R1628P Mutations Are Associated with an Increased Risk of Parkinson's Disease in the Malaysian Population. (27th August 2014) - Gopalai, Aroma Agape; Lim, Shen-Yang; Chua, Jing Yi; Tey, Shelisa; Lim, Thien Thien; Mohamed Ibrahim, Norlinah; Tan, Ai Huey; Eow, Gaik Bee; Abdul Aziz, Zariah; Puvanarajah, Santhi Datuk; Viswanathan, Shanthi; Looi, Irene; et al.
Abstract : The LRRK2 gene has been associated with both familial and sporadic forms of Parkinson's disease (PD). The G2019S variant is commonly found in North African Arab and Caucasian PD patients, but this locus is monomorphic in Asians. The G2385R and R1628P variants are associated with a higher risk of developing PD in certain Asian populations but have not been studied in the Malaysian population. Therefore, we screened the G2385R and R1628P variants in 1, 202 Malaysian subjects consisting of 695 cases and 507 controls. The G2385R and R1628P variants were associated with a 2.2-fold (P = 0.019 ) and 1.2-fold (P = 0.054 ) increased risk of PD, respectively. Our data concur with other reported findings in Chinese, Taiwanese, Singaporean, and Korean studies.